Nitric oxide augments signaling for contraction in hypoxic pulmonary arterial smooth muscle—Implications for hypoxic pulmonary hypertension - Hinton, Martha; Thliveris, James A.; Hatch, Grant M.; Dakshinamurti, Shyamala (Frontiers in Physiology, 2023)
Hypoxic persistent pulmonary hypertension in the newborn (PPHN) is usually treated with oxygen and inhaled nitric oxide (NO), both pulmonary arterial relaxants. But treatment failure with NO occurs in 25% of cases. We previously demonstrated that 72 h exposure to hypoxia, modeling PPHN, sensitized pulmonary artery smooth muscle cells (PASMC) to the contractile agonist thromboxane and inhibited relaxant adenylyl cyclase (AC) activity. In this study, we examined the effects of sodium nitroprusside (SNP), as NO donor, on the thromboxane-mediated contraction and NO-independent relaxation pathways and on reactive oxygen species (ROS) accumulation in PASMC. In addition, we examined the effect of the peroxynitrite scavenger 5,10,15,20-Tetrakis(4-sulfonatophenyl)porphyrinato Iron (III) (FeTTPs) on these processes. Exposure of PASMC to 72h hypoxia increased total intracellular ROS compared to normoxic control cells and this was mitigated by treatment of cells with either SNP or FeTTPs. Total protein nitrosylation was increased in hypoxic PASMC compared to controls. Both normoxic and hypoxic cells treated with SNP exhibited increased total protein nitrosylation and intracellular nitrite; this was reduced by treatment with FeTTPs. While cell viability and mitochondrial number were unchanged by hypoxia, mitochondrial activity was decreased compared to controls; addition of FeTTPs did not alter this. Basal and maximal mitochondrial metabolism and ATP turnover were reduced in hypoxic PASMC compared to controls. Hypoxic PASMC had higher basal Ca2+, and a heightened peak Ca2+ response to thromboxane challenge compared to controls. Addition of SNP further elevated the peak Ca2+ response, while addition of FeTTPs brought peak Ca2+ response down to control levels. AC mediated relaxation was impaired in hypoxic PASMC compared to controls but was normalized following treatment with FeTTPs. Addition of SNP inhibited adenylyl cyclase activity in both normoxic and hypoxic PASMC. Moreover, addition of the Ca2+ chelator BAPTA improved AC activity, but the effect was minimal. We conclude that NO independently augments contraction and inhibits relaxation pathways in hypoxic PASMC, in part by a mechanism involving nitrogen radical formation and protein nitrosylation. These observations may partially explain impaired effectiveness of NO when treating hypoxic pulmonary hypertension.